Nag Hammadi Codices XI, XII, XIII - Hedrick, Charles W. (Nag Hammadi Studies, 1990)
This volume presents critical editions of three of the most fragmentary codices in the Nag Hammadi Library. Their nine tractates are presented in an English translation with critically edited transcriptions of Coptic texts, including introductions and notes. A complete set of indices is provided for Coptic and Greek words, proper names, ancient texts and authors, and modern authors. The contents of these three ancient books reflect the rich diversity of the Library as a whole. They include a fragmentary (and apparently non-Christian) revelation descent narrative ( Hypsiphrone ); a non-Christian Sethian text reflecting heavy platonizing influence ( Allogenes ); Hellenistic Greek wisdom literature ( Sentence of Sextus ); a non-christian Sethian text, secondarily Christianized ( Trimorphic Protennoia ); Valentinian Gnosticism ( A Valentinian Exposition ); a Christian-Gnostic tractate with Valentinian affinities ( The Interpretation of Knowledge ). A Christian-Gnostic (perhaps Valentinian) homily on the gospel (the Gospel of Truth ); the first page of On the Origin of the World (completely preserved in NHC II) and an identified fragmentary tractate with ethical content. There are also five Valentinian liturgical supplements appended to Allogenes . The publication of these religio-philosophical materials from Nag Hammadi provides the scholar and interested reader with critical editions of texts that help to fill in background and context of gnostic origins, and that shed light on the interaction among early Christianity and gnostic movements in antiquity.